Implementation of Home Medication Review in Patients with Chronic Diseases: A Pilot Study in Indonesia - Mega Silviana; Vitarani Dwi Ananda Ningrum; Okti Ratna Mafruhah (Journal of Pharmaceutical Care)
Background: The high prevalence of chronic diseases such as diabetes mellitus, hypertension, and dyslipidemia is a concern for pharmacists. Pharmacists are expected to participate in these efforts by implementing Home Medication Review (HMR). HMR is a community-based collaborative service outside of health facilities that involves physicians and pharmacists to improve the effectiveness of therapy. This study aimed to determine the incidence of drug-related problems (DRPs), the level of patient satisfaction, and the effect of improving the quality of life of patients with chronic diseases who received Home Medication Review services at the Banjarbaru Utara Primary Health Care.